JBCPS in 2021-2022: How The Editorial Board Worked, What Is Done and The Aspirations! (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Abstract not availableJ Bangladesh Coll Phys Surg 2023; 41: 98-99